Evaluation of MQL performances using various nanofluids in turning of AISI 304 stainless steel - Touggui, Youssef; Uysal, Alper; Emiroglu, Ugur; Belhadi, Salim; Temmar, Mustapha (SPRINGER LONDON LTD, 2021)
In recent years, the need for eco-friendly machining processes has increased dramatically in order to limit the excessive use of conventional cutting fluids, thereby reducing their negative effects on both the environment and the operator's health. In this context, environmental alternatives such as dry cutting, minimum quantity lubrication (MQL), and nanofluid-assisted MQL have been demonstrated to be effective in overcoming this problem. In the present work, an attempt was made to improve the machining characteristics performance in turning of AISI 304 austenitic stainless steel (ASS) under dry, MQL and nanofluids, and hybrid nanofluid-assisted MQL conditions, with respect to surface roughness (Ra), main cutting force (Fc), and cutting temperature (T). The main purpose of this experimental study is to evaluate and compare the effect of dispersed nano-additives into the vegetable cutting fluid on the responses under consideration. As nano-additives, multi-walled carbon nanotube (MWCNT), nano molybdenum disulfide (MoS2), and nano graphene particles have been used. Additionally, the effects of lubricating conditions on flank wear (VB) were investigated. In the end, statistical analysis, regression modeling, and multi-criteria optimization based on desirability function were performed. The results revealed that the Ra, Fc, and T as well as VB were found to be lower with the use of nano graphene-reinforced nanofluid-assisted MQL followed by nano graphene/MoS2-reinforced hybrid nanofluid-assisted MQL, MWCNT/MoS2-reinforced hybrid nanofluid-assisted MQL, MWCNT-reinforced nanofluid-assisted MQL, nano MoS2-reinforced nanofluid-assisted MQL, and MQL, respectively, as compared to dry condition. Finally, it is worth mentioning that the nano graphene has the capability to perform as a lubricant/coolant, thus contributing positively to the turning process.
Keywords: Nanofluid; MQL method; Nano MoS2; MWCNT; Nano graphene; Stainless steel; Turning; HYBRID NANOPARTICLE ADDITIVES; SURFACE-ROUGHNESS; TRIBOLOGICAL PROPERTIES; STAINLESS-STEEL; CUTTING FLUID; GRAPHENE; MACHINABILITY; WEAR; DRY; OPTIMIZATION; Automation & Control Systems; Engineering